The influence of Allee effect, refugia, and alternative food on a three-species predator-prey model - Rohmatunnisa, Haya; Asih, Tri Sri Noor; Waluya, Stevanus Budi; Safaatullah, Muhammad Fajar (Universitas Negeri Semarang, 2023)
This research presents a mathematical model for a three-species predator-prey system, incorporating the Allee effect, refugia, and alternative food. The interactions between prey and intermediate predator, as well as intermediate predator and top predator, are modeled using Holling type II response functions. The resulting system of nonlinear equations yields four equilibrium points, one unstable and three stable locally. Analytical calculations indicate that refugia and alternative food minimally affect the top predator's population growth, while the Allee effect influences the growth of prey and intermediate predator populations. Numerical simulations further support these findings, highlighting the nuanced impacts of these factors on the dynamics of the three-species system.